The Understanding Ability of Exercises of Higher Order Thinking Skill-Based Anecdote Text in 10th Grade Students of Senior High School 1 Tanjung Tiram - Cica Elida Hanum Matondang; Wisman Hadi; Malan Lubis (BIRCU, 2019)
The aim of this study is to know the understanding ability of exercises of higher order thinking skill-based anecdote text in 10th grade students of senior high school 1 Tanjung Tiram. This study was conducted in the odd semester of the 2018/2019 academic year which was planned starting from the collection of knowledge data to the writing as a whole. The subjects of this study were 10th grade students of Senior High School 1 Tanjung Tiram as many as 30 students. The object carried out in this study is a guide to higher order thinking skill (HOTS)-based knowledge instruments. The result shows that the understanding ability of exercises of higher order thinking skill-based anecdote text the students get an average score of 60.56% in the